Relationship of the Gonial Angle and Inferior Alveolar Canal Course Using Cone Beam Computed Tomography - Najmeh Anbiaee; Farzaneh Eslami; Ali Bagherpour (Tehran University of Medical Sciences, 2016)
Objectives: Accurate localization of the inferior alveolar canal (IAC) is extremely important in some dental treatments. Anatomical variation of the canal means that it can be difficult to locate. The purpose of this study was to assess the relationship of the gonial angle (GA) size and IAC position using cone beam computed tomography (CBCT). Materials and Methods: In this in vitro study, 61 dry adult human hemi-mandibles were used. The CBCT scans were taken of all samples and GA was measured on all CBCT scans. The samples were divided into two groups of low angle (≤125°) and high angle (>125°). The canal dimensions, length and course were evaluated. On the sagittal view, the IAC path was classified as type A, B or C. On the axial view, canal course was defined as A1 or A2 according to the mental foramen angle. Results: The average GA size was 121.8±7.05° at the right side and 123.8±6.32° at the left side. On the sagittal view, there was a significant correlation between the GA size and the canal course (P=0.04). In the high-angle group, type A was dominant; whereas in the low-angle group, type B was more common. On the axial view of IAC course, type A1 was more common (73.43%). Conclusion: The results showed that GA size was associated with IAC course. In cases with a larger GA, the canal runs in a more straightforward path, and at the same level as the mental foramen. Keywords: Cone Beam Computed Tomography; Mandibular Nerve; Mandible